Java - based Sony Ericsson phone book manager using bluetooth / Farahani Che Khosni - Che Khosni, Farahani (Faculty of Computer and Mathematical Sciences, 2005)
Bluetooth is a new wireless technology with high speed of connection for exchanging data between devices, such as mobile phone with personal computer. As people who live in the development country, mobile phone also becomes one of the important things, which they must have in their life. Unfortunately, their phones may be damaged or being stolen. They will lose all the important data especially the contact names and numbers. Because of the importance of the mobile phone, this thesis is conducted to give solution for phone book manager for Sony Ericsson's mobile phone. This research is conducted using Java-based platform and using Bluetooth features to synchronizes the data. This research is critically done as to make a back up for the Sony Ericsson's phone book manager and to make the data is easier to manage inside the computer. In conclusion, we can say that the data, which we get from the phone, is much easier to manage inside the computer, and we have given the solutiort of limited phone book spaces.